Metagenomic evidence for the microbial transformation of carboxyl-rich alicyclic molecules: A long-term macrocosm experiment. (1st June 2022) - He, Changfei; Liu, Jihua; Wang, Rui; Li, Yuanning; Zheng, Qiang; Jiao, Fanglue; He, Chen; Shi, Quan; Xu, Yongle; Zhang, Rui; Thomas, Helmuth; Batt, John; et al.
Highlights: A long-term macrocosm incubation uncovers microbial DOM transformation pathway. Leucine metabolism facilitates efficient Carboxyl-rich alicyclic molecules production. Acetyl-CoA and 3-Hydroxy-3-methylglutaryl-CoA are main substrates for isopentenyl-PP. The mevalonate pathway is the key path producing carboxyl-rich alicyclic molecules. Abstract: Carboxyl-rich alicyclic molecules (CRAMs) widely exist in the ocean and constitute the central part of the refractory dissolved organic matter (RDOM) pool. Although a consensus has been reached that microbial activity forms CRAMs, the detailed molecular mechanisms remain largely unexplored. To better understand the underlying genetic mechanisms driving the microbial transformation of CRAM, a long-term macrocosm experiment spanning 220 days was conducted in the Aquatron Tower Tank at Dalhousie University, Halifax, Canada, with the supply of diatom-derived DOM as a carbon source. The DOM composition, community structure, and metabolic pathways were characterised using multi-omics approaches. The addition of diatom lysate introduced a mass of labile DOM into the incubation seawater, which led to a low degradation index (IDEG ) and refractory molecular lability boundary (RMLB) on days 1 and 18. The molecular compositions of the DOM molecules in the later incubation period (from day 120 to day 220) were more similar in composition to those on day 0, suggesting a rapid turnover of phytoplankton debris by microbial communities. Taxonomically, while Alpha proteobacteria dominated during the entire incubation period, Gamma proteobacteria became more sensitive and abundant than the other bacterial groups on days 1 and 18. Recalcitrant measurements such as IDEG and RMLB were closely related to the DOM molecules, bacterial community, and Kyoto encyclopaedia of Genes and Genomes (KEGG) modules, suggesting close associations between RDOM accumulation and microbial metabolism. KEGG modules that showed strong positive correlation with CRAMs were identified using a microbial ecological network approach. The identified KEGG modules produced the substrates, such as the acetyl-CoA or 3‑hydroxy-3-methylglutaryl-CoA, which could participate in the mevalonate pathway to generate the precursor of CRAM analogues, isopentenyl-PP, suggesting a potential generation pathway of CRAM analogues in bacteria and archaea. This study revealed the potential genetic and molecular processes involved in the microbial origin of CRAM analogues, and thus indicated a vital ecological role of bacteria and archaea in RDOM production. This study also offered new perspectives on the carbon sequestration in the ocean. Graphical abstract: Image, graphical abstract